Cultural values and romantic relationship satisfaction in Mexican adolescents: The moderating effects of parental psychological control and gender. (6th November 2019) - Reid, Alexander; Halgunseth, Linda C.; Espinosa‐Hernández, Graciela; Csizmadia, Annamaria; Card, Noel
ABSTRACT: Introduction: Cultural values and parent‐adolescent relationships may impact adolescents' romantic relationship quality. The goal of this study was to examine whether perceived mothers' and fathers' psychological control and gender moderated associations between cultural values (i.e., machismo, caballerismo, views of female virginity) and romantic relationship satisfaction in Mexican adolescents. Methods: Self‐report survey data were collected from 213 adolescents ( M  = 14.59 years old; 50.5% girls) from two public schools in Mexico. All participants were in a romantic relationship at time of study, and reported on their age, gender, endorsement of cultural values (i.e., machismo, caballerismo, views of female virginity), perceived parental psychological control, and romantic satisfaction. Exploratory and confirmatory factor analyses were conducted on a romantic relationship satisfaction scale. Multiple regression analyses were conducted to assess interactions between cultural values, mothers' and fathers' psychological control, and gender on romantic relationship satisfaction. Results: Findings revealed adolescents who endorsed caballerismo reported higher relationship satisfaction. These associations were strongest for adolescent girls reporting low maternal psychological control and adolescent boys reporting high maternal psychological control. Perceived fathers' psychological control did not moderate associations between cultural values and romantic satisfaction. No associations were found between machismo, female virginity, and romantic relationship satisfaction. Conclusion: Adolescents' caballersimo values were linked to higher relationship satisfaction. Findings suggest that parent education programs in Mexico may benefit from teaching parents to instill values of caballerismo in their romantically involved adolescents. Additionally, specialists working with Mexican adolescent girls may help them reframe perceived psychologically controlling behaviors into attempts to communicate affection.